Digital Government Enterprise Strategies at the Regional Drinking Water Company (PDAM) Delta Tirta, Sidoarjo Regency, Indonesia - Putri, Devi Erlinda Artama; Kriswibowo, Arimurti (JPSI (Journal of Public Sector Innovations), 2024)
This study examines the digital government enterprise strategies at the Regional Drinking Water Company (PDAM) Delta Tirta, Sidoarjo Regency, Indonesia. PDAM Delta Tirta faces problems in achieving its water service coverage target, serving only a small proportion of the total population. In addition, the PDAM’s implementation of e-government has not been optimal, reflected in the low rating of its digital services. This problem reflects a lack of effectiveness in implementing digital government strategies, which should improve the quality of public services and operational efficiency. This study used a descriptive qualitative research method with snowball sampling to select six key informants. Data were analysed using an interactive model that included data collection, condensation, data presentation, and drawing conclusions. The results showed that PDAM Delta Tirta's digitalisation strategy is supported by the Chief Information Officer (CIO) role and cross-field collaboration for infrastructure innovation. However, there are still constraints on budget allocation and human resource development. However, the commitment to quality service, reflected in the high Public Satisfaction Index (PSI) in 2023, confirms the importance of understanding public values and stakeholder needs in successful digitisation.